Study on physical prediction model of liquid film development and dry out point in helical tube - Rui, Min; Chen, Tianming; Zhou, Mingjia; Zheng, Xiong; Hu, Yisong; Jin, Desheng; Hu, Yousen; Mao, Yulong (Frontiers in Energy Research, 2023)
Helical tubes are widely used in nuclear plants, heat recovery process, refrigeration technology, etc. It is obtained the helical tubes dry out point prediction model in accordance with the experimental conditions by numerical simulation. The article is based on the physical model of the liquid membrane in the helical tube before dry out happened, establishing the analytical process of liquid film development in helical tube. The physical mechanism, thermo-hydraulic parameters that affect liquid film crushing are analyzed. The dry out point of helical tubes is predicted based on the experimental data. The result shows that the geometrical, thermo-hydraulic parameters of helical tube will affect the occurrence of the dry out point, the development process of liquid film before evaporation of spiral tube is obtained. The prediction model of dry out point is fitted to experimental data and the predicted results of evaporation point can be used to optimize during the engineering design.